Foraging Behaviour of Some Papilionid Butterflies in Bhawal and Madhupur Sal Forests of Bangladesh - Chowdhury, MAK (Journal of Biodiversity Conservation and Bioresource Management, 2021)
Foraging behaviour of nine papilionid butterflies have been studied from two moist deciduous sal forests viz. Bhawal and Madhupur from central part of Bangladesh. Papilionid butterflies were found to visit 156 flowering plant species belong to 39 plant families. Dependency of papilionid butterflies on flowering plants varied from family to family with high dependency on family Asteraceae (15%) followed by Rubiaceae (8%), Rutaceae (6%), Verbenaceae (6%), Apocynaceae (6%) and Fabaceae (6%). Although most of the plant species (72 species, 47.68%) were visited by single butterfly species but some were also visited by multiple species of butterflies (e.g., Chromolaena odorata by 9 species, followed by Mikania cordata and Lantana camara by 8 and 7 species, respectively). Ninety eight percent (153 out of 156 species) of the nectar resources were dicotyledonous in origin but two percent plant species (three out of 156 species under three families) were monocotyledonous. Six floral attributes such as plants life forms, nature, perennation, origin, corolla shape and flower massing contributed butterflies significantly to visit plants for nectaring. J. Biodivers. Conserv. Bioresour. Manag. 2020, 6(2): 55-68